The Challenges of Teaching and Learning the Igbo Language at Chukwuemeka Odumegwu Ojugwu University, Igbariam Nigeria - Udoye, Ifeoma, Emmanuela (My University, 2019)
This study identifies and describes the problems of teaching and learning of the Igbo language at Chukwuemeka Odumegwu Ojukwu University, Nigeria. In the last two decades, it has been observed that there has been a substantial decrease in the proportion of students who applied for or even enrolled to study the Igbo language at university level in Nigeria. Using survey design, this study investigated the problems associated with the teaching and learning of the Igbo language. Fifteen Igbo language students and four Igbo language lecturers at Chukwuemeka Odumegwu Ojukwu University, Igbariam campus were used to obtain information. Two instruments were administered on participants selected for the study. Results indicate that lack of Igbo pedagogical materials, attitude of people towards the language among other things prevent the smooth teaching and learning of the Igbo language. The paper concludes that although efforts are made by scholars to revitalize and popularize the study of Igbo language, interest and enrolment among prospective students are still very low.
Keywords: Igbo language; learning; teaching; language; students; university